2013
DOI: 10.3109/0886022x.2013.830206
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nutritional status, physical function, comorbidity and early versus late start in dialysis on quality of life in older dialysis patients

Abstract: Our results indicate that physical function is important to all QoL aspects. Increased focus on physical rehabilitation seems pertinent. Early start of dialysis treatment was not associated with better long term QoL scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
1
14
0
5
Order By: Relevance
“…3,4 Nutritional deficits and diet restrictions are frequent problems that imply negative health outcomes with high mortality risk and QOL deterioration. 7 Poor physical health and mental health are highly reported in this population and the latter is an independent risk factor for mortality in patients on dialysis. 1,4 Physical function decline is a prevalent feature in HD population and seems to affect negatively QOL even for younger HD patients.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Nutritional deficits and diet restrictions are frequent problems that imply negative health outcomes with high mortality risk and QOL deterioration. 7 Poor physical health and mental health are highly reported in this population and the latter is an independent risk factor for mortality in patients on dialysis. 1,4 Physical function decline is a prevalent feature in HD population and seems to affect negatively QOL even for younger HD patients.…”
mentioning
confidence: 99%
“…3,4 The assessment of QOL of ESRD patients (physical, mental, and social well-being) has become an essential tool to develop better plans of care (preventive and treatment strategies) and a recommended routine clinical practice. 1,6 Comorbid disorders are prevalent in chronic kidney disease patients, such as depression (30% of ESRD patients), sexual dysfunction (nearly half of ESRD), and problems with sleep (up to 40%-80%), ranging from insomnia, sleep apnea to restless leg syndrome, and are associated with mortality as well as QOL, 7 all of which contribute to worse QOL. Nutritional status is an important determinant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless in the systematic review done by Spiegel and colleagues, they concluded that nutritional biomarkers including creatinine and albumin had a strong correlation with the physical domains of the HRQOL in ESRD patients [38]. Therefore, it is essential to maintain the nutritional parameters and physical performance emphasizing on physical rehabilitation for an overall wellbeing of patients [39].…”
Section: Discussionmentioning
confidence: 99%
“…Enquanto, no domínio lista de sintomas e o escore total do KDQOL-SF, aqueles com IMC<25kg/m², tiveram melhores resultados. Quando comparado com outros estudos (KALANTAR-ZADEH et al, 2001;LAEGREID et al, 2014;RAMOS et al, 2015), o presente teve melhor escore no componente mental. Com relação aos sintomas da doença renal, deve-se ressaltar o aumento das dores musculares, cãibras, falta de ar e fraqueza relatados durante o preenchimento do questionário, que são sintomas esperados em maior ou menor intensidade na clínica do paciente.…”
Section: Discussionunclassified